Los nudos de Garcilaso: kipu y escritura en los Comentarios reales (siglo XVII) [Crítica] - Favaron Peyón, Pedro Martín (2026)
This article offers a philosophical reflection based on an analysis of Inca Garcilaso de la Vega’s discourse regarding the Andean nodal notation system known as kipu. To this end, it first reviews selected passages from the Comentarios Reales in which the characteristics of this archival method are described, highlighting its importance for Inca administration. The main focus of the analysis, however, lies in the attempt to uncover the internal logic behind Garcilaso’s explicit discursive contradictions and his ongoing comparison between phonological writing and kipus. Subsequently, still following the reading of Comentarios Reales, the study examines the inseparable link between the nodal system and the mathematical, architectural, and astronomical development of ancient Andean societies. It emphasizes that this native science did not lead to a mechanistic conception of the cosmos but rather emerged within an ontological reflection in which humans could ritually connect to the sacred web of life. In this way, the article demonstrates that Amerindian peoples were not illiterate societies; they had their own technical systems for creating archives, which allowed them to perform advanced calculations without breaking from a broad cosmogonic worldview in which all existence possessed life and intelligence and formed part of a single existential fabric.